Foreign Influence and Domestic Policy - Aidt, Toke S.; Albornoz, Facundo; Hauk, Esther (Journal of Economic Literature, 2021)
In an interconnected world, economic and political interests inevitably reach beyond national borders. Since policy choices generate external economic and political costs, foreign state and non-state actors have an interest in influencing policy actions in other sovereign countries to their advantage. Foreign influence is a strategic choice aimed at internalizing these externalities and takes three principal forms: (i) voluntary agreements, (ii) policy interventions based on rewarding or sanctioning the target country to obtain a specific change in policy, and (iii) institution interventions aimed at influencing the political institutions in the target country. We propose a unifying theoretical framework to study when foreign influence is chosen and in which form, and use it to organize and evaluate the new political economics literature on foreign influence along with work in cognate disciplines (JEL D72, D74, F51, F53, P26, P33).